Comperative Legal Analysis Regarding Efforts To Prevent Sexual Violence And Legal Protection For Women In The Credit And Law Number 12 Of 2022 Concerning Actions Criminal Sexual Violence - Venny Zahara; Muhammad Arif Sahlepi; Redyanto Sidi (CV. AFDIFAL MAJU BERKAH, 2024)
Sexual violence is a criminal act which basically requires very strict law enforcement. The dimensions of sexual violence regulated in the Criminal Code are not yet able to fully regulate the forms of sexual violence that occur, where regulations related to sexual violence are regulated in articles 281-295 of the Criminal Code which have limited clarification. on rape and molestation. So, with the enactment of law number 12 of 2022 concerning criminal acts of sexual violence (UU TPKS) on May 9 2022, it becomes the new legal basis for enforcing criminal acts of sexual violence. The TPKS Law becomes a specialist Lex for regulations previously contained in the Criminal Code. The presence of the TPKS Law is a new positive law that provides clear and specific updates regarding the types of criminal acts that are classified as criminal acts of sexual violence, the rights of victims of criminal acts of sexual violence, as well as protection for victims of criminal acts of sexual violence in law enforcement. The formulation of the problem in this research is how to compare legal regulations and legal protection between the Criminal Code and Law number 12 of 2022 regarding criminal acts of sexual violence. This research uses normative juridical research methods, using secondary data sources, with primary legal materials in the form of related laws which are supported by secondary legal materials in the form of related books and journals. Based on the results of this research, the research results will be summarized as to what the position of victims is. criminal acts of sexual violence which are in the Criminal Code and Law no. 12 of 2002 which regulates different legal provisions and legal protection which in the Criminal Code is not clearly regulated regarding legal protection for victims of criminal acts of sexual violence which in law number 12 of 2002 is clearly regulated regarding the protection of victims and prevention efforts against the occurrence of criminal acts of sexual harassment.